Protection and communication abstractions for web browsers in MashupOS - Wang, Helen; Howell, Jon (SOSP, 2007)
Web browsers have evolved from a single-principal platform on which one site is browsed at a time into a multi-principal platform on which data and code from mutually distrusting sites interact programmatically in a single page at the browser. Today’s “Web 2.0” applications (or mashups) offer rich services, rivaling those of desktop PCs. However, the protection and communication abstractions offered by today’s browsers remain suitable only for a single-principal system—either no trust through complete isolation between principals (sites) or full trust by incorporating third party code as libraries. In this paper, we address this deficiency by identifying and designing the missing abstractions needed for a browser-based multi-principal platform. We have designed our abstractions to be backward compatible and easily adoptable. We have built a prototype system that realizes almost all of our abstractions and their associated properties. Our evaluation shows that our abstractions make it easy to build more secure and robust client-side Web mashups and can be easily implemented with negligible performance overhead.